Effects of Calcium Bentonite on High Blood Cholesterol Level - Hendro Sudjono Yuwono; Fadhli Rajif Tangke; Reni Farenia (Althea Medical Journal, 2018)
Background: Calcium bentonite has been known to decrease high blood cholesterol level. This study aimed to explore whether a local calcium bentonite from West Java, Indonesia, had effect on lowering total blood cholesterol level.Methods: A laboratory experimental study was carried out on thirty adult male  Wistar rats’ at Laboratory animals, Department of Pharmacology and Therapy, Universitas Padjadjaran in 2012. The rats were divided into five groups with six rats in each group, consisting of group I (negative control) with standard diet and distilled water, group II (positive control) with high lipid diet and distilled water, group III with high lipid diet and ezetimibe 0.18 g/rat/day, groups IV with high lipid diet and calcium bentonite 0.25 g/rat/day, group V with high lipid diet and calcium bentonite 0.5 g/rat/day. Ezetimibe as was used as this was an inhibitory agent of intestinal cholesterol absorption. Blood cholesterol levels were measured and analyzed using analysis of variance and Tukey’s post-hoc test.Results: Oral calcium bentonite at 0.25 g/rat/day and 0.5 g/rat/day significantly decrease total blood cholesterol level relative to the positive control group, 31.68% (p=0.018) and 32.87% (p=0.006) respectively, but its effect is inferior to ezetimibe 62.83% (p=0.000).Conclusions: Local calcium bentonite from West Java, Indonesia, has a significant lowering effect, however, the effect is less comparing to ezetimibe.